HAMBATAN EPISTEMOLOGI PADA PEMBUKTIAN GEOMETRI SEDERHANA SISWA SMP DITINJAU DARI RESILIENSI MATEMATIS - Safira Dinda Fitria; Samsul Maarif (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Lack of information regarding mathematical knowledge obtained by students can result in these students experiencing epistemological obstacles. Meanwhile, the mathematical resilience possessed by students can help students get more information about mathematical knowledge that they have not completely obtained. This research methodology is included in descriptive qualitative research where the data collection technique is by using the Pythagorean theorem test method, mathematical resilience questionnaire and interviews. There were 23 respondents in this study who were students of class VIII 280 Senior High School. In this study the data were analyzed by identifying the answers of 23 respondents to the indicators of epistemological barriers and the mathematical resilience questionnaire that had been done by the students, then interviewing 6 respondents. The results of this study are that there are three types of students' epistemological obstacles in proving the Pythagorean theorem.